4 - (0) = y
4 - 0 = 4 y = 4
4 - (1) = y
4 - 1 = 3 y = 3
4 - (2) = y
4 - 2 = 2 y = 2
4 - (3) = y
4 - 3 = 1 y = 1
Answer:
b = 5.
Step-by-step explanation:
-3(6 + 6b) + 4 = -104
-18 - 18b + 4 = -104
-18b = -104 + 18 - 4
-18b = -90
b = -90 / -18
b = 5.
Answer:
It's the second one I believe, because it's not a straight line, and nearly all functions have curved lines
Step-by-step explanation:
Answer:
C F
Step-by-step explanation:
Answer: X=2
Step-by-step explanation:
Assuming the function is
All logarithmic functions, despite their base, has a vertical asymptote at argument = 0.
That is not changed by the vertical stretching made by the 4 which multiplies the logarithm nor the vertical shift made by the +5.
In this case the argument is x - 2, then the vertical asymptote is:
x - 2 = 0